Enhancing Management Accounting Practices in Manufacturing Companies: A Special Reference to Top-level Management - Khan, Imran (Asian Business Review, 2018)
Management accounting facilitates efficient business operation deploying different techniques that deal with the competitive edge. Organizations are facing new challenges regularly. To survive and expand business management always focus on different traditional and contemporary managerial techniques including. The management accounting techniques incorporate standard costing and variance analysis, traditional budgeting and cost volume profit analysis are commonly applied by managers which are now considered to be less useful in the competitive manufacturing environment. In order to achieve organizational goal and succeed in this present dynamic business environment, new techniques or strategies such as Just-In-Time (JIT), Activity Based Costing (ABC), Total Quality Management (TQM), process re-engineering, life cycle assessment and target costing would accelerate the capability of organizations by overcoming the acute global competition. This paper is an empirical study on manufacturing companies. Overall, the evidence reveals that most of the top-level management rely on so-called traditional techniques in their day to day activities than that of contemporary management accounting tools. However, new tools could accelerate business operations faster. Therefore, it is vivid that application of traditional management accounting techniques holds a strong position in the manufacturing arena. However, there is a good sign that some third generation businesses are trying to utilize new techniques slowly. Moreover, there exists some areas where proper attention is required to ensure best practice and utilization of management accounting mechanism. According to the findings, this paper provides some recommendations that might be useful to enhance the effectiveness and competitiveness of the top-level management and thus helpful in ensuring the practice of more sophisticated techniques in regular business operation.